IMPROVING WRITING SKILL THROUGH THINK PAIR SHARE AND CUE CARD - I Kadek Wira Dana; Putu Ayu Paramita Dharmayanti (Academic Journal on English Studies (AJOES), 2021)
Writing is one of the language skills that should be learnt by the students beside otherlanguage skills. Its purpose is to communicate the language in written form. Regarding theimportant of writing, in fact, writing still becomes which was conducted to the tenth gradestudents of SMK Dwijendra Denpasar in academic year 2019/2020 needed to be improvedthrough think pair share and cue card. The present study was conducted in two cycles. The datawere gathered by administering pre-test and post-test. The results of the post-tests in each cycleobviously showed that there were significant improvements concerning the subject’ ability inwriting skill. Furthermore, the additional findings showed that most of the subjects gave positiveresponses toward the implementation of think pair share and cue card in improving their writingability. In conclusion, the present classroom action research proved that the writing skill of thetenth grade student of SMK Dwijendra Denpasar in academic year 2019/2020 can be improvedthrough think pair share and cue card.